Kuantan Singingi Botanical Garden Dengan Pendekatan Parametrik Desain - Suryander, Ridho; Husaini, Muhd. Arief Al; Susilawaty, Mira Dharma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Indonesia is a country with a tropical climate. The tropical climate makes Indonesia rich in natural resources, especially the diversity of flora that are scattered throughout Indonesia. Indonesia is estimated to have 25% of the species of flowering plants around the world. Exploitation of flora diversity, illegal logging, conversion of forest areas to other areas, hunting and illegal trade are some of the factors that cause the endangerment of flora diversity. To prevent more and more flora from becoming extinct and to study flora species we need a container, namely a botanical garden. The approach used to design a botanical garden is a parametric design approach. This approach is used to solve the problem of placement of space, structure, and expand human thinking in creating formations. Keywords : Botanical Garden, Parametric Design, Flora Diversity